From First ‘True’ Yugoslavs to Last Yugoslavs. Paradoxes of Socialist Youth Politics and Culture in the 1980s (KULT_online, 2018)
In her analysis of the political and cultural activity of Yugoslavs born between 1954 and 1969, the author contends that there was a genuine support for a more liberal and democratic version of socialism, due to the decentralized nature and diplomatic positioning of Yugoslavia. Three main characteristics defined their outlook: economic and political crisis, internationalist and European aspirations, and new understanding of what it meant to be a Yugoslav citizen. With its combination of archival sources, press materials, public surveys, and oral history interviews, the book offers an important contribution to research on youth agency in politics and culture.